Which Fixation Device is Preferred for Surgical Treatment of Intertrochanteric Hip Fractures in the United States? A Survey of Orthopaedic Surgeons. Issue 11 (November 2015) - Niu, Emily; Yang, Arthur; Harris, Alex H. S.; Bishop, Julius
Abstract: Background: The best treatment for intertrochanteric hip fractures is controversial. The use of cephalomedullary nails has increased, whereas use of sliding hip screws has decreased despite the lack of evidence that cephalomedullary nails are more effective. As current orthopaedic trainees receive less exposure to sliding hip screws, this may continue to perpetuate the preferential use of cephalomedullary nails, with important implications for resident education, evidence‐based best practices, and healthcare cost. Questions/purposes: We asked: (1) What are the current practice patterns in surgical treatment of intertrochanteric fractures among orthopaedic surgeons? (2) Do surgical practice patterns differ based on surgeon characteristics, practice setting, and other factors? (3) What is the rationale behind these surgical practice patterns? (4) What postoperative approaches do surgeons use for intertrochanteric fractures? Methods: A web‐based survey containing 20 questions was distributed to active members of the American Academy of Orthopaedic Surgeons. Three thousand seven‐hundred eighty‐six of 10, 321 invited surgeons participated in the survey (37%), with a 97% completion rate (3687 of 3784 responded to all questions in the survey). The survey elicited information regarding surgeon demographics, preferred management strategies, and decision‐making rationale for intertrochanteric fractures. Results: Surgeons use cephalomedullary nails most frequently for treatment of intertrochanteric hip fractures. Sixty‐eight percent primarily use cephalomedullary nails, whereas only19% primarily use sliding hip screws, and the remaining 13% use cephalomedullary nails and sliding hip screws with equal frequency. The cephalomedullary nail was the dominant approach regardless of experience level or practice setting. Surgeons who practiced in a nonacademic setting (71% versus 58%; p < 0.001), did not supervise residents (71% versus 61%; p < 0.001), or treated more than five intertrochanteric fractures a month (78% versus 67%; p < 0.001) were more likely to use primarily cephalomedullary nails. Of the surgeons who used only cephalomedullary nails, ease of surgical technique (58%) was cited as the primary reason, whereas surgeons who used only sliding hip screws cite familiarity (44%) and improved outcomes (37%) as their primary reasons. Of those who use only short cephalomedullary nails, ease of technique (59%) was most frequently cited. Postoperatively, 67% allow the patient to bear weight as tolerated. Nearly all respondents (99.5%) use postoperative chemical thromboprophylaxis. Conclusions: Despite that either sliding hip screw or cephalomedullary nail fixation are associated with equivalent outcomes for most intertrochanteric femur fractures, the cephalomedullary nail has emerged as the preferred construct, with the majority of surgeons believing that a cephalomedullary nail is easier to use, associated with improved outcomes, or is biomechanically superior to a sliding hip screw. The difference between what is evidence‐based and what is done in clinical practice may be attributed to several factors, including financial considerations, educational experience, or inability of our current outcomes measures to reflect the experiences of surgeons. The educators, researchers, and policymakers among us must work harder to better define the roles of sliding hip screws and cephalomedullary nails and ensure that the increasing population with hip fractures receives high‐quality and economically responsible care. Level of Evidence: Level V, therapeutic study.